Qualitative Assessment of Diffusion Weighted Imaging and Susceptibility Weighted Imaging of Myeloid Sarcoma Involving the Brain. Issue 1 (January 2016) - Chaudhry, Ammar A.; Gul, Maryam; Chaudhry, Abbas A.; Dunkin, Jared
Abstract : Background and Purpose: Myeloid sarcoma is a rare form of extramedullary leukemia, which can present with or without systemic leukemia. The purpose of this study was to evaluate characteristic computed tomography (CT) and magnetic resonance imaging (MRI) findings (including diffusion weighted imaging and susceptibility weighted imaging) of myeloid sarcoma involving the brain. Materials and Methods: One hundred nine patients with pathologically proven myeloid sarcoma underwent pretreatment CT and MRI, which were retrospectively reviewed. Computed tomography and MRI characteristics reviewed include lesion location, shape, size, architecture, margins, ±multiplicity, ±bone destruction, pattern and degree of enhancement, ±restricted diffusion, and ±susceptibility artifact. Results: Twenty-five patients (14 men, 11 women; mean age, 55 years; range, 9–80 years) met the inclusion criteria. Acute myeloid leukemia with subtypes M3 (44.4%) and M5 (22.2%) were the most common. On unenhanced CT, mean lesion size was 1.9 ± 0.4cm; 60% were intra-axial hyperdense masses, 8% were intraventricular hyperdense masses, 12% were isodense intra-axial masses, and 20% of cases were extra-axial hyperdense nodular masses. There was no observable intralesional or perilesional calcium. On MRI, mean lesion size was 2.1 ± 0.6cm. The lesions were isointense (80%) or hypointense (20%) on T1-weighted images with homogeneous (88%) or heterogeneous (12%) enhancement. On fluid-attenuated inversion recovery and T2-weighted images, lesions were hyperintense (96%) or isointense (4%) with mild vasogenic edema. Majority (96%) of cases demonstrated restricted diffusion, whereas only a few (16%) demonstrated susceptibility artifact. Conclusions: In patients with history of leukemia or myeloproliferative disorder, identification of homogenous mass hyperdense on unenhanced CT, T1 isointense, and T2/fluid-attenuated inversion recovery hyperintense with restricted diffusion and homogenous postcontrast enhancement without significant susceptibility artifact is suggestive of myeloid sarcoma.